因式分解:(x+1)(x+3)(x+2)(x+4)-3

2025-01-07 15:07:41
推荐回答(5个)
回答1:

=(x+1)(x+4)(x+3)(x+2)-3
=(x^2+5x+4)(x^2+5x+6)-3 a=x^2+5x
=(a+4)(a+6)-3
=a^2+10a+21
=(a+3)(a+7)
=(x^2+5x+3)(x^2+5x+7)

希望我粗陋的回答能帮到你!(还有不懂的,可以在线叫我,我一般都在) *^o^*

回答2:

解:原式=(x+1)(x+4)*(x+2)(x+3)+1-4
=(x^2+5x+4)(x^2+5x+6)+1-4
=(x^2+5x+4)[(x^2+5x+4)+2]+1-4
=(x^+5x+4)^2+2(x^2+5x+4)+1-4
=[(x^2+5x+4)+1]^2 -4
=(x^2+5x+5)^2-4
=(x^2+5x+7)(x^2+5x+3)

回答3:

=(x2+4x+3)(x2+6x+8)-3
=x4+6x3+8x2+4x3+24x2+32x+3x2+18x+24-3
= x4+10x3=35x2+50x=21

回答4:

原式=(x+1)(x+4)(x+3)(x+2)-3
=(x2+5x+4)(x2+5x+6)-3
把x2+5x当作a
则(a+4)(a+6)-3=a2+10a+21=(a+3)(a+7)
再把a变成x2+5x。

回答5:

(x+1)(x+2)(x+3)(x+4)-3
=(x^2+5x+4)(x^2+5x+6)-3

两两结合得到
=(x^2+5x)^2+10(x^2+5x)+21

把x^2+5x当成整体乘进去
=(x^2+5x+3)(x^2+5x+7)十字相乘法